OGC P27 A Review of Minimally Invasive Oesophagogastric Cancer Surgery in a High-Volume UK Unit. (7th December 2022) - Chana, Prem; Ni, Melody Zhifang; Moore, Jonathan; Baker, Cara; Kelly, Mark; Davies, Andrew; Gossage, James
Abstract: Background: Oesophagogastric (OG) cancer resections are technically challenging and associated with peri-operative morbidity. Practice has evolved from open to minimally invasive surgery (MIS), with ERAS has seen peri-operative outcomes improve. OG surgeons have not transitioned to MIS at the rate of others; 2021 NOGCA results showed that 17.6% of oesophagectomies and 17% of gastrectomies were performed as MIS. Concerns regarding the technical ability to perform safe anastomoses and appropriate oncological clearance have been cited as common reasons for surgeons not transitioning to MIS. GSTT is a high-volume OG unit which has transitioned from a fully open to predominantly MIS practice. The unit has performed over 100 minimally invasive Ivor Lewis oesophagectomies and 97 laparoscopic gastrectomies, it was therefore decided to analyse the unit's peri-operative outcomes to ensure that appropriate standards were maintained during this change in practice. The primary aim of this study was to examine a decade of peri-operative outcomes for Ivor Lewis oesophagectomy and gastrectomies, comparing parallel open and MIS cohorts. The secondary aim is to perform a sequential cumulative sum control chart (CUSM) analysis of the cohort to determine whether a learning curve effect for OG MIS can be demonstrated. Methods: A retrospective analysis of a prospectively maintained comprehensive local database was performed. The results were cross-checked with NOCGA data, and a notes review was performed to capture any missing data.All Ivor Lewis oesophagectomy and gastrectomy (total, extended total and subtotal) performed for adenocarcinoma, squamous cell carcinoma, neuroendocrine tumours and high grade dysplasia at Guy's and St Thomas' NHS Foundation Trust, London, UK over a ten-year period (January 2012- December 2021) were included. MIS for oesophagectomy was defined as an Ivor Lewis oesophagectomy performed with both laparoscopic and thoracoscopic phases. A hybrid (laparoscopic abdomen and open chest phase) oesophagectomy was grouped with a two-phase open procedure to create an open cohort. Laparoscopic gastrectomy (with a laparoscopic oesophago-jejunostomy or gastro-jejunostomy for sub-total gastrectomy) was used as the definition of MIS. The cohorts were compared for: age, sex, BMI and use of neoadjuvant therapy. Temporal trends in surgical approaches were compared as were Individual surgeon (n=4) volumes. Peri-operative clinical and oncological outcomes including length of stay, anastomotic leak, return to theatre, chest complications, resection margins and lymph node harvest were all examined. A CUSM analysis is currently being completed to further analyse surgeon performance over time. Results: 596 patients underwent resection in well matched cohorts, 197 patients had an oesophagectomy (100 MIO), 339 had a gastrectomy (97 laparoscopic). MIS rates increased with no operations being performed as MIS in 2012 compared to 81% of oesophagectomy and 67% of gastrectomy performed as MIS in 2021. Two surgeons performed over 170 resections with MIS rate over 40%. OR of MIS performed by a high-volume surgeon was 3.01 (p<0.001). Lower volume MIS surgeons were more likely to have two consultants present, OR 1.4 (p=0.16). Anastomotic leak rates following gastrectomy were 2% in both groups (p=0.66), 9% following open oesophagectomy and 11% after MIO (p=0.77). 10% of laparoscopic gastrectomy patients experienced a chest complication, 26% after open surgery, 22% MIO and 24% open (p=0.65). Mean length of stay was significantly reduced after MIS. An R0 rate of 96% was seen after laparoscopic gastrectomy, 90% after open (p=0.08). 68% of MIO patients had R0 resection compared to 70% after open. Positive CRM was 29% after MIO. The mean lymph node harvest was 29 after laparoscopic gastrectomy and 26 after open (p=0.24), 29 following MIO, 30 after open oesophagectomy. 97% of MIO harvested over 15 nodes. Conclusions: This study demonstrates that a transition from open to MIS practice is achievable in the UK. Outcomes demonstrated similar peri-operative clinical and oncological outcomes between MIS and open surgery which addresses the concerns that prohibited the widespread uptake of MIS in UK centres. Developing a reliable surgical technique for lymphadenectomy and anastomoses that transitioned from open to hybrid and now MIS allowed for appropriate outcomes to be maintained. Unit outcomes compare well to both NOGCA/ECCG data with complication rates following MIO being significantly lower when compared to ECCG. Lymph node harvests were significantly higher in unit MIOs when compared to NOGCA (p=0.01). Volume played an important role in surgeons performing independent MIS. This should be considered when planning unit workload or a transition to MIS. It will be further explored in the CUSM analysis. A positive CRM was seen in more cases (29%) when compared to NOGCA (24%) and may be related to the preferred neoadjuvant regime being chemotherapy over chemoradiotherapy. The future of OG is moving towards robotic surgery. It is proposed that the evolution from open to MIS will make a second transition to robotics less challenging as the strategies needed to perform MIS have been addressed.